The effects of chronic neuroleptic treatment on neurotensin-like immunoreactivity in the rat central nervous system. - Goedert, M; Iversen, S; Emson, P (1985)
The dopamine receptor antagonist fluphenazine decanoate, when administered for a total period of 10 months, produced a large increase in neurotensin-like immunoreactivity in dopamine-rich brain areas, such as the nucleus accumbens, the striatum and the frontal cortex. A smaller, non-significant increase was observed in the substantia nigra with no change in either the hypothalamus or the spinal cord. The present results provide further evidence in favour of a functional interaction between neurotensin and dopamine in the central nervous system.